Glutamate metabolism and HIV-associated neurocognitive disorders - Vázquez-Santiago, Fabián J.; Noel, Richard J.; Porter, James T.; Rivera-Amill, Vanessa (Journal of neurovirology, 2014)
HIV-1 infection can lead to neurocognitive impairment collectively known as HIV-associated neurocognitive disorders (HAND). Although combined antiretroviral treatment (cART) has significantly ameliorated HIV’s morbidity and mortality, persistent neuroinflammation and neurocognitive dysfunction continue. This review focuses on the current clinical and molecular evidence of the viral and host factors that influence glutamate-mediated neurotoxicity and neuropathogenesis as an important underlying mechanism during the course of HAND development. In addition, discusses potential pharmacological strategies targeting the glutamatergic system that may help prevent and improve neurological outcomes in HIV-1-infected subjects.